A Simple Ansatz to Predict the Structure of Li4Ti5O12. Issue 2 (22nd December 2016) - Zahn, Stefan; Janek, Jürgen; Mollenhauer, Doreen
Abstract : The titanium-based anode material Li4 Ti5 O12 is an alternative to carbon based anode materials in cells for fast charging lithium ion batteries (LIB). Li4 Ti5 O12 exhibits a negligible volume change during Li-uptake to Li7 Ti5 O12 . In order to understand lithium diffusion in the solid state or at interfaces, first principles calculations can provide a detailed picture at the atomistic level. Therefore, it is important to know the preferred lithium substitution pattern of the materials, as lithium and titanium share the 16d Wyckoff positions in Li4 Ti5 O12 and Li7 Ti5 O12 . We show by first principles calculations that strain inside the material is increased when lithium replaces titanium on the 16d Wyckoff positions in Li4 Ti5 O12 . This allows to predict the most stable Li substitution pattern of Li4 Ti5 O12 for which the lithium atoms are distributed as homogeneous as possible over all planes of the system. Similarities and differences to Li7 Ti5 O12 regarding the structural setup have been studied and discussed.